Thin Film Deposition on Open‐Cell Foams by Atmospheric Pressure Dielectric Barrier Discharges. Issue 4 (5th October 2015) - Fanelli, Fiorenza; Fracassi, Francesco
Abstract : Thin films are deposited on open‐cell polyurethane (PU) foams using an atmospheric pressure dielectric barrier discharge (DBD) fed with helium and hexafluoropropene (C3 F6 ). During deposition processes, a foam substrate is sandwiched between the dielectric‐covered electrodes of a parallel plate DBD reactor, so that the discharge can ignite also inside its three‐dimensional (3D) interconnected porous structure. This affords the deposition of a fluorocarbon coating on both the exterior and interior of the foam. Scanning electron microscopy (SEM) observations allow estimating the thickness of the coating deposited on the foam struts, while X‐ray photoelectron spectroscopy (XPS) analyses show moderate changes in surface chemical composition moving from the outer to the inner surfaces of the plasma‐treated foams under all explored experimental conditions. Abstract : Fluorocarbon coatings are deposited on open‐cell polyurethane foams using an atmospheric pressure dielectric barrier discharge fed with helium and hexafluoropropene. The discharge is ignited both outside and inside the three‐dimensional porous structure of the foam, so that thin film deposition can be achieved on both its outer and inner surfaces.